O declínio da função paterna nas redes sociais: uma leitura semiótico-psicanalítica - Sampaio, Maria do Carmo Cardoso (2016)
This thesis presents the study of signs and symptoms related to paternal role in the contemporary societies. For this, we started with the hypothesis that this function is in decline that manifests itself in the media and many forms of entertainment such as films, television, and in the advertising images etc. By allowing direct access to what people think and feel. The chosen media for this research was the Facebook. In order to track the thematic and look for empirical to support the hypothesis mentioned. The theoretical foundations of this research were searched in Freud and Lacan. Facebook posts were selected and analyzed. The symbolic function of the real father determines one of the fundamental bases of psychoanalytic clinic. The readings of the statements in addition to the background of psychoanalytic studies were based on the theories of semiotics, art and technology in order to unveil the simulations in the language on Facebook social network. The analysis raises some of the statements in categories such as love and religion. These convergences reveal that the social network Facebook is also a cultural phenomenon created to avoid the malaise in civilization and simulate the father's convalescence weakened libidinally. This convalescence takes place through demonstrations of users who post, like, share and comment. It provides users the conditions for production signs of love. The real sex needs to have surveillance “phantasmatic” look of Facebook Social Network that clings to the password Love, marking human sexuality with an irreducible failure. And showing that sexual difference is the antagonism of the two sexual positions between which there is no common denominator, the enjoyment can only be achieved against a fundamental loss